TINJAUAN SISTEMATIS EFEKTIVITAS GAME EDUKASI BERBASIS MOBILE UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA SMP DI INDONESIA - Nining Dian Santiasih; I Nyoman Sukajaya; I Nyoman Budayana; I Made Suarsana (Universitas Muria Kudus, 2026)
This study aims to examine the effectiveness of mobile-based game learning media on junior high school students’ mathematical conceptual understanding in Indonesia. The research employed a Systematic Literature Review (SLR) method following the PRISMA protocol, which includes identification, screening, eligibility, and inclusion stages. The literature search was conducted through Google Scholar and other relevant databases within the publication range of 2022–2026. Based on the predetermined inclusion and exclusion criteria, four relevant articles were selected for analysis. The results indicate that mobile game-based learning media are generally effective in improving students’ conceptual understanding of mathematics. This effectiveness is reflected in improved learning outcomes, deeper conceptual comprehension, and the transformation of abstract concepts into more concrete forms through visualization and interactivity. In addition, the use of educational games positively influences students’ motivation, interest, and engagement in the learning process. However, the level of effectiveness is influenced by several factors, including technological readiness, students’ prior knowledge, and instructional strategies applied by teachers. Therefore, mobile-based game learning media have strong potential as an innovative approach to support meaningful mathematics learning at the junior high school level.